Evaluation of novel bitter cassava film for equilibrium modified atmosphere packaging of cherry tomatoes. (September 2017) - Tumwesigye, K.S.; Sousa, A.R.; Oliveira, J.C.; Sousa-Gallagher, M.J.
Graphical abstract: Highlights: Bitter cassava film equilibrium atmosphere (EMAP) design requirements of cherry tomatoes. Impact of EMAP design parameters on gas composition of cherry tomatoes. Unperforated IBC film achieved desirable EMAP gas composition of cherry tomatoes. Optimal IBC film EMAP extended the shelf life of cherry tomatoes to 19 days. Bio-based IBC film offers new possibilities for packaging and in marketing of fresh produce. Abstract: Equilibrium modified atmosphere packaging (EMAP) technology offers the possibility to maintain produce postharvest quality and extend its shelf-life. However, EMAP stability depends on well-tuned packaging design parameters to match environment conditions. This study defined design requirements of a biobased film EMAP that can preserve quality and prolong shelf-life of fresh cherry tomatoes under recommended and simulated abuse supply chain conditions. Optimum EMAP was evaluated based on headspace gas composition at 10–20 °C, 75–95% RH and verified by determining quality changes of packed cherry tomatoes in using a continuous or micro-perforated (0.27 μm) bio-based intact bitter cassava (IBC) film. This was compared with a non-bio-based polymer film (oriented polypropylene, OPP). The IBC film attained equilibrium O2 (2–3%) after 180 h at 10 °C, with 0 and 1 perforation, for 75 and 95% RH while OPP film maintained a downward O2 fall. Continuous and micro-perforated IBC film did not show any major differences in equilibrium headspace O2, thus perforation can be neglected. Based on desirability optimisation results, biobased IBC film demonstrated better optimized EMAP system in attaining recommended gas and stretching cherry tomato shelf-life as compared to non-biobased (OPP) film. The application of bio-based IBC film offers new possibilities in packaging fresh produce under equilibrium modified atmosphere without compromising their quality.